2019
DOI: 10.1093/jnci/djz173
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Oncologist Discussions of the Costs of Genomic Testing and Related Treatments

Abstract: Background Use of genomic testing is increasing in the United States. Testing can be expensive, and not all tests and related treatments are covered by health insurance. Little is known about how often oncologists discuss costs of testing and treatment or about the factors associated with those discussions. Methods We identified 1220 oncologists who reported discussing genomic testing with their cancer patients from the 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…We dichotomized patient volume as , 100 and ≥ 100 patients consistent with the literature. 22 Payer mix was identified from one item asking respondents to indicate what proportions of their patients were insured by Medicaid, or self-pay or uninsured. We dichotomized payer mix into , 10% and ≥ 10% Medicaid, or self-pay or uninsured.…”
Section: Covariates-patient Volume and Payer MIXmentioning
confidence: 99%
“…We dichotomized patient volume as , 100 and ≥ 100 patients consistent with the literature. 22 Payer mix was identified from one item asking respondents to indicate what proportions of their patients were insured by Medicaid, or self-pay or uninsured. We dichotomized payer mix into , 10% and ≥ 10% Medicaid, or self-pay or uninsured.…”
Section: Covariates-patient Volume and Payer MIXmentioning
confidence: 99%
“…We therefore calculated the percent at which HYP and diabetes contributed to the racial disparity in OS between WA and BA CC patients. The results showed that HYP and diabetes explained 19.6% and 12% of disparities, respectively ( Table 3), suggesting that there are additional factor(s) that explain the remaining two-thirds of disparity between WA and BA [1][2][3][4][5][6][7]. Although HYP or diabetes alone is not a main contributor to the racial disparity in OS for our cohort, our results show that HYP is an independent factor for shorter OS in CC (Table 2).…”
Section: Discussionmentioning
confidence: 69%
“…In the United States, there is disparity for colorectal cancer (CRC) incidence and mortality between races, with Black Americans (BA) exhibiting higher rates as compared to White Americans (WA) [1][2][3][4][5]. Current evidence suggests that the contributions to this disparity is multi-factorial, intertwining socioeconomic issues that affect medical insurance coverage, access to preventive and regular medical care, use of tobacco and alcohol, and ingesting a high fiber, lower red meat diet that can affect the gut microbiome and cancer risk [2,[5][6][7]. Pathological and biological analyses show disparity in tumor stage contributing to earlier mortality, potential modification of the local tumor immunological environment, as well as unique somatic genetic mutations that appear isolated in BA CRC patients [1,3,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And, even when germline testing is covered by insurance, there may be prohibitive out-of-pocket costs, including deductibles and copayments. Additionally, not all insurers cover germline testing for PCa [ 46 ], including some private insurers and public options such as Medicare and Medicaid [ 64 ].…”
Section: Reasons For the Disparities In Germline Testing Among Racial/ethnic Minorities With Pca And Potential Strategies To Bridge The Gmentioning
confidence: 99%